2012
DOI: 10.1016/j.jembe.2012.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of light availability on mixotrophy and microzooplankton grazing in an oligotrophic plankton food web: Evidences from a mesocosm study in Eastern Mediterranean waters

Abstract: Plankton biomass and composition in the pelagic zone of oceans is exposed to changes in availability of light and nutrients due to large-scale ocean circulation and water column stratification. We hypothesized that displacement of plankton from surface to deeper darker waters would not only favor heterotrophy over time, as previously suggested, but also first rapidly affect the level of mixotrophy and, consequently, overall microbial grazing in plankton food webs. To test this in an oligotrophic marine system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 71 publications
(63 reference statements)
0
36
1
1
Order By: Relevance
“…In consequence, field measurements of mixotrophy need to deploy mixed tracers (i.e. not solely C tracers) and use a variety of approaches (Zubkov and Tarran, 2008;Calbet et al, 2012). Furthermore, significant changes in photosynthesis may or may not be expected (depending on the fate of the prey C).…”
Section: Interpreting the Simulationsmentioning
confidence: 99%
“…In consequence, field measurements of mixotrophy need to deploy mixed tracers (i.e. not solely C tracers) and use a variety of approaches (Zubkov and Tarran, 2008;Calbet et al, 2012). Furthermore, significant changes in photosynthesis may or may not be expected (depending on the fate of the prey C).…”
Section: Interpreting the Simulationsmentioning
confidence: 99%
“…The increasing abundance of cells of sizes > 6 µm can be explained by alleviation of top-down control, as the most important grazers in this size range, cladocerans and copepods (Bautista & Harris 1992, Liu et al 2005, Souza et al 2005, Mercado et al 2007) were removed at the beginning of the experiment. Furthermore, mesozooplankton also prey on microzooplankton (Calbet & Landry 1999, Calbet et al 2012. The proportion of microzooplankton in the copepod diet is highly variable (Halvorsen et al 2001) and depends mainly on the phytoplankton and zooplankton size structure.…”
Section: Cascade Effects In the Enclosed Communitymentioning
confidence: 99%
“…Generally, manipulation of bottom-up factors changed microbial growth rates, but the presence or absence of micrograzers was the most important determinant of carbon biomass. Calbet et al (2012) studied the effects of light availability on mixotrophy and microzooplankton grazing in an oligotrophic plankton food web in a mesocosm study in the Eastern Mediterranean waters, and observed that the decrease in nutritional quality of phytoplankton in mesocosms at high irradiance (higher C:chlorophyll ratios) was not reflected in a lower final abundance of grazers (both micro-and mesozooplankton). The authors pointed out that further work is needed in order to better understand the effect of light availability on Mediterranean aquatic food webs.…”
Section: Introductionmentioning
confidence: 99%